Sensitization to amphetamine psychostimulant effect: A key role for ventral tegmental area neurotensin type 2 receptors and MAP kinase pathway - Voyer, David; Einsiedel, Jürgen; Gmeiner, Peter; Lévesque, Daniel; Rompré, Pierre Paul (Addiction Biology, 2021)
Neurotensin is an endogenous neuropeptide that acts as a potent modulator of ventral tegmental area (VTA) neurotransmission. The present study was aimed at determining VTA cell population and neurotensin receptor subtype responsible for the initiation of amphetamine-induced psychomotor activity and extracellular signal-regulated kinases (ERK1/2) sensitization. During an induction phase, rats were injected intra-VTA on two occasions, every second day, with [D-Tyr11]-neurotensin (D-Tyr-NT), SR142948 (a mix Ntsr1/Ntsr2 receptor subtype antagonist), SR48692 (a Ntsr1 antagonist), D-Tyr-NT + SR142498, D-Tyr-NT + SR48692, or the vehicle. Effects of intra-VTA drugs were evaluated at locomotor activity and ERK1/2 phosphorylation. Five days after the last VTA microinjection, the effect of a systemic injection of amphetamine was tested (sensitization test). Results show that D-Tyr-NT stimulated locomotor activity during the induction phase, an effect that was blocked by SR142948, but not SR48692. Amphetamine also induced significantly higher ambulatory activity in rats preinjected with D-Tyr-NT than in rats preinjected with the vehicle. This sensitization effect was again attenuated by SR142948, but not SR48692, hence suggesting that this effect is mediated by Ntsr2 receptors. To confirm this, we tested a highly selective Ntsr2 peptide–peptoid hybrid ligand, NT150. At the concentration tested, NT150 stimulated locomotor activity and lead to sensitized locomotor activity and a selective neurochemical (pERK1/2) response in tyrosine hydroxylase-positive neurons of the VTA. Both effects were prevented by SR142948. Taken together, these results show that neurotensin, acting on Ntsr2 receptor subtypes, stimulates locomotor activity and initiates neural changes (ERK1/2 phosphorylation) that lead to amphetamine-induced sensitization.
CRIS-Team Scopus Importer:2021-02-05
Keywords: dopamine neuron; ERK1/2 phosphorylation; locomotor activity; Ntsr2; pharmacological tools; VTA